Research in Action: From AIDS to Global Health to Impact. A Symposium in Recognition of the Scientific Contributions of Professor Joep Lange. Issue 1 (January 2015) - Boender, T Sonia; Barré-Sinoussi, Françoise; Cooper, David; Goosby, Eric; Hankins, Catherine; Heidenrijk, Michiel; De Jong, Menno; Kazatchkine, Michel; Laoye, Fola; Merson, Michael; Reiss, Peter; De Wit, Tobias F Rinke; et al.
On Tuesday 14 October 2014, 850 family members, friends, colleagues, prominent scientists and dignitaries from all over the world gathered in Amsterdam to pay tribute to the lives and legacies of Joep Lange and Jacqueline van Tongeren. The remembrance was held at the Amsterdam Medical Centre (AMC) where Joep and Jacqueline met and worked together for many years. The day was organized by the AMC, the Amsterdam Institute for Global Health and Development (AIGHD) and PharmAccess Foundation. The latter two were both founded by Joep. A morning symposium titled 'Research in action: from AIDS to global health to impact' highlighted Joep's scientific legacy (Figure 1). During the remembrance in the afternoon, a range of speakers shared memories of Joep and Jacqueline. As was the case during their lives, the personal and the professional were closely intertwined throughout the day. As Prof Peter Piot said, Joep and Jacqueline shared a common perspective on life: 'La folie suprême est de voir la vie comme elle est et non comme elle devrait être.' If there was one thing that defined them both, it was indeed that they saw life – and lived it – not as it was, but as it should be. 'Joep's place in history is really as the visionary architect of combination therapy, ' Prof Piot stated, adding that 'it cannot be stressed enough that he was ahead of his time, a true innovator.' Joep's contribution didn't stop at science. Dr Khama Rogo of the World Bank explained that 'it's not enough to be a doctor or a researcher if you're not also an activist.' Joep fully understood the importance of translating research into action and generating impact for people. Prof Marcel Levi, chairman of the AMC, summarized the enormity of the impact Joep had on the world with the words 'it's rare to know someone who has saved millions of lives.' The scientific symposium traced Joep's career, starting in the early eighties with the treatment of the first AIDS patients and the design of antiretroviral therapy, moving towards the emerging field of global health and ending with his most recent focus: using knowledge derived from scientific research to improve access to quality health care in real-world settings. From Prof Françoise Barré-Sinoussi, who won the Nobel Prize for the discovery of HIV, to Prof Michael Merson, who founded Duke University's Global Health Institute, the list of presenters reads like a who's who of people involved at key moments in the history of HIV and global health (Figure 2). 'And Joep, ' as Barré-Sinoussi said, 'contributed to all eras of HIV.' More memories of Joep and Jacqueline shared throughout the day are available athttp://www.joepandjacqueline.org/remembrance/ .